Responsible management in Africa. volume 2, - Ogunyemi, Kemi; Ogunyemi, Omowumi; Anozie, Amaka (Emerald Publishing Limited, 2022)
Africa is one of the world's oldest economies, yet little is known about the wisdom that traditionally guided responsible management, with most work in the field employing Western perspectives. Responsible Management in Africa brings African voices to complement existing knowledge and practice by presenting indigenous values and practices that promote responsible business. Following on the first volume of Responsible Management in Africa which brought together insights from Zimbabwe, South Africa, Nigeria, Ghana, Egypt, Lesotho and Uganda, this volume brings unique perspectives from another set of varied African contexts: traditions, culture, and values guiding business in Mauritius, Zambia and Namibia, the sustainability orientation of the Igbo Apprenticeship System in Nigeria, and principled social responsibility practices in Algeria. It also highlights the CSR experience in Kenya and inclusive trust-based credit systems in Tanzania and explains the viability of traditional African health systems. The chapters present academic perspectives and hands-on applications of approaches to managing responsibly, especially regarding integrating ethical practices into business and assuring sustainability through ethical profitability. Responsible Management in Africa delivers a rich reservoir of indigenous value-narratives based on a well-balanced philosophical anthropology, with the aims of enriching global knowledge, in the philosophy of management and in business ethics, and of contributing much-needed insights for leaders around the world to manage enterprise responsibly, be it public or private sector.